(untitled) - Sharpe, Pamela J.; Pamela J.Sharpe (Tp. Hồ Chí Minh, 2006)
This new 11th edition offers complete and up-to date preparation for the Paper-Based TOEFL and the Computer-Based TOEFL, with a preview of the Next Generation TOEFL test. There is extensive practice-even for students who don't have access to a computer. The manual includes a review chapter for each section of the TOEFL, including the new Speaking Section, and presents nine full-length model tests for the Computer-Based TOEFL, with questions answered and explained, along with one full-length model test for the Next Generation
Keywords: TOEFL; TOEFL (Test of English as a Foreign Language)